Model updating of gun recoil mechanism based on time domain response. (April 2020) - Liu, J; Xu, H Y; Zhou, C J; L, Y; Liu, P K; He, Q
Abstract: For gun launching dynamics modeling, the accuracy of the recoil and counterrecoil model is important. In order to improve the accuracy of gun recoil mechanism modeling, the rigid-flexible coupling firing dynamics model of a small-caliber gun was established, and the recoil displacement of the gun was tested by live firing test. Aiming at the error between the simulation curve and the test curve of the recoil displacement changing with time, taking the correlation coefficient of the two curves as the objective function, the dynamics model of the recoil mechanism was modified based on the time-domain response using the optimization algorithm. The modified results show that the difference of the maximum recoil displacement decreases from 9% to 0.1%, and the similarity between the simulation curve and the test curve reaches 0.99. The modified results based on the time-domain response effectively improve the accuracy of the recoil model, so that the established dynamics model can more truly reflect the dynamic characteristics of the recoil mechanisms, and provide the basic conditions for ensuring the simulation accuracy of the launch dynamics model.